Relevance of the Ministry of Religious Affairs' Religious Education Curriculum: Analysis of Knowledge, Skills, and Policy Implementation Gaps - Agustiningsih, Dwi (POKJANAS PERENCANA KEMENTERIAN AGAMA RI, 2025)
This policy paper aims to analyze the gap between the religious education curriculum implemented by the Ministry of Religious Affairs and the knowledge and skills needs of students in the digital era. The background of this problem is the lack of relevance of the curriculum to current developments that require students to have digital literacy, critical thinking skills, and multicultural understanding. The research method used is a qualitative approach with case studies in several madrasahs and public schools in Indonesia, involving in-depth interviews with teachers, students, and policymakers, as well as analysis of curriculum documents. The results of the study indicate a significant gap, where teaching materials tend to focus on theoretical aspects and memorization, while practical skills and the implementation of religious values ​​in daily life are still minimal. Further discussion highlights that the implementation of curriculum policies is often hampered by a lack of teacher training, inadequate supporting facilities, and resistance to change. The conclusion of this study is that the current religious education curriculum requires substantial reform to be more relevant and adaptive to contemporary challenges. Recommendations include developing a competency-based curriculum, strengthening teacher training programs, integrating technology into learning, and developing more participatory policies.